The Protocols Concerning the Settlement of Trade Disputes in the Euro-Mediterranean Area - Miguel Ángel Cepillo Galvín (Paix et Sécurité Internationales, 2018)
In 2010 and 2011, the European Union signed a series of Protocols with Tunisia, Lebanon, Egypt and Jordan, and an Agreement with Morocco, concerning the settlement of trade disputes that might arise in application of the Euro-Mediterranean Association Agreements signed with these countries.